Identification of candidate cardiomyopathy modifier genes through genome sequencing and RNA profiling - Lindholm, Malene E.; Abramowitz, Sarah; Waggott, Daryl M.; Grove, Megan E.; Dewey, Frederick E.; Pan, Cuiping; Pavlovic, Aleksandra; Shang, Ching; Huang, Yong; Bensabath, Leore; Goldfeder, Rachel L.; Cordero, Pablo; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPhenotypic heterogeneity is apparent among individuals with putative monogenic disease, such as familial hypertrophic cardiomyopathy. Genome sequencing (GS) allows interrogation of the full spectrum of inborn genetic variation in an individual and RNA profiling provides a snapshot of the cardiac-specific pathogenic effects on gene expression.ObjectivesIdentify candidate genetic modifiers of hypertrophic cardiomyopathy phenotype.MethodsWe performed GS of 48 individuals with variants in MYH7, the gene encoding beta myosin heavy chain, and a personal or family history of cardiomyopathy. The genome sequences were annotated with a custom pipeline optimized for cardiovascular gene variant detection. We utilized multiple lines of evidence to prioritize genes together with rare variant gene-based association testing to identify candidate genetic modifiers.ResultsGS identified the MYH7 variant in all 48 cases. Several variants were reclassified based on best available data. We identified known disease-associated genes (MYBPC3, FHOD3), a priori candidate modifiers (ATP1A2, RYR2), and novel candidate modifiers of cardiomyopathy including PACSIN3 and SORBS2. We identified regulatory variants and intergenic regions associated with the phenotypes. Using RNA profiling, we show that several genes identified through gene-based association testing are differentially regulated in human hypertrophic cardiomyopathy, and in models of disease.ConclusionEvaluation of the whole genome, even in the case of alleged monogenic disease, leads to important new insights. The identified variants, regions, and genes are candidates to modify disease presentation in cardiomyopathy.